Thrace through the ages : pottery as evidence for commerce and culture from prehistoric times to the Islamic period - Koçel Erdem, Zeynep,; Şahin, Reyhan, (Archaeopress Archaeology, 2023)
This volume draws attention to the importance of pottery evidence in evaluating archaeological material from Thrace. It considers the informative value of pottery in tracing cultural and political phases, by providing us with important data about production centres, commercial relations, daily life, religious rituals and burial customs.